Exploration of Trademark Conflict of Use on the Internet - Kaige Zheng (Law and Economy, 2024)
The Internet has changed the traditional business model and become the main channel for enterprises to promote their goods and build up their goodwill, which has led to an increase in the number of trademark right conflicts worldwide. The resolution of trademark right conflicts has put forward new requirements for trademark law, and it seems that the traditional trademark coexistence system can be regarded as an effective way to solve the conflicts of trademark rights on the Internet.